Application of Problem Based Learning to Improve Student Motivation and Learning Outcomes on Vector Material - Torang Siregar (Saniya Institute, 2024)
This class action research aims to measure the increase in student motivation and learning outcomes by using the Problem Based Learning model on Vector material in Class X SMAN 1 Yogyakarta. In the implementation of learning Mathematics Specialization of vector comparison material in Cycle II, there was a significant increase in student learning outcomes. Students have met the Minimum Completeness Criteria (KKM ≥ 75) with a class average of more than 80%, as evidenced by the results obtained by 17 students in cycle II. The average score increased from 74 in cycle I to 83 in cycle II, up 9 points. The number of students who scored ≥ 75 increased from 8 to 16 students, with an increase of 8 students and a percentage from 47% in cycle I to 94% in cycle II. Meanwhile, students with scores < 75 decreased from 9 to only 1 student below the KKM. Based on this data, it can be concluded that the application of Problem Based Learning model succeeded in increasing students' motivation and learning outcomes on vector material in class X MIPA-1 SMAN 1 Yogyakarta. Therefore, the researcher decided not to continue the action in the next cycle because the learning process was as expected.